Black Women's Perspectives on Structural Racism across the Reproductive Lifespan: A Conceptual Framework for Measurement Development. - Chambers, Brittany D.; Arega, Helen A.; Arabia, Silvia E.; Taylor, Brianne; Barron, Robyn G.; Gates, Brandi; Scruggs-Leach, Loretta; Scott, Karen A.; McLemore, Monica R. (Maternal & Child Health Journal, 2021)
Background: Exposures to structural racism has been identified as one of the leading risk factors for adverse maternal and infant health outcomes among Black women; yet current measures of structural racism do not fully account for inequities seen in adverse maternal and infant health outcomes between Black and white women and infants. In response, the purpose of this study was to conceptualize structural racism from the perspectives of Black women across the reproductive lifespan and its potential impact on adverse maternal and infant health outcomes. Methods: We conducted a series of focus groups with 32 Black women across the reproductive lifespan (5 preconception, 13 pregnant, and 14 postpartum). Study criteria including self-identifying as Black, residing in Oakland or Fresno, California and representing one of three reproductive life tracks (preconception, pregnant, postpartum). We consulted with study participants and an expert advisory board to validate emergent domains of structural racism. Results: Nine domains of structural racism emerged from a ground theory constant comparative analysis: Negative Societal Views; Housing; Medical Care; Law Enforcement; Hidden Resources; Employment; Education, Community Infrastructure; and Policing Black Families. Conclusions for Practice: Findings from this study suggest that there is an interplay among structural racism, and social and structural determinants of health which has negative impacts on Black women's sexual and reproductive health. Furthermore, findings from this study can be used to develop more comprehensive medical assessments and policies to address structural racism experienced by Black women across the reproductive lifespan.